Family‐based social capital of emerging adults with and without mild intellectual disability. Issue 10 (3rd August 2020) - Giesbers, S. A. H.; Hendriks, A. H. C.; Hastings, R. P.; Jahoda, A.; Tournier, T.; Embregts, P. J. C. M.
Abstract: Background: Family is recognised as an important context for the self‐development of young adults in emerging adulthood, although very little research has addressed the perspective of young people with intellectual disability about their families by using self‐report. This study examined how emerging adults with mild intellectual disability define their family support networks, compared with definitions of students without intellectual disability, within a social capital theoretical framework. Methods: Fifty‐three participants with mild intellectual disability and 53 students without intellectual disability were interviewed individually using the Family Network Method – Intellectual Disability (FNM‐ID). Data from the FNM‐ID relate to key social network measures on how individuals define their family groups, and how they perceive existing supportive relationships within their families. Participants with mild intellectual disability and students were compared on the FNM‐ID social network measures. Results: Participants with mild intellectual disability reported fewer family members who they considered significant to them than students without intellectual disability. They were less likely to include peers (i.e. friends and partners) and siblings in their significant family networks, had fewer relationships with family members in which they received or gave support, had fewer reciprocal support relationships and had a less central position in their family network. Discussion: The family‐based social capital of emerging adults with mild intellectual disability differed from that of students without intellectual disability. They may remain more dependent on their natural family for emotional support as their supportive networks have not necessarily made the transition to networks with emotionally close peer relationships.